(untitled) (Research, Society and Development, 2021)
Orotracheal intubation is considered the most delicate maneuver performed by anesthesiologists, and failure to manage the airways is one of the main causes of possible complications that can be catastrophic during its performance, thus requiring good team planning. Anatomical and / or physiological characteristics, such as limited mouth opening, a condition often found in patients suffering from fractures of the zygomatic arch or who have some abnormality in the temporomandibular joint (TMJ), can characterize a difficult airway, which demands attention greatest of the professional. Therefore, in order to overcome the obstacles that may occur during a difficult or unexpected intubation, new tools have been used, such as videolaryngoscopy in which an intubation device containing miniature video cameras is used in order to allow the operator has an indirect view of the glottis to increase success rates and decrease intubation time. The aim of the present study is to report a clinical case of a trauma victim, with limited mouth opening, who underwent intubation with the aid of a video laryngoscope after failed attempts at conventional intubation.